Global collective action in health: The WDR+20 landscape of core and supportive functions - Nathan Blanchet; Milan Thomas; Rifat Atun; Dean Jamison; Felicia Knaul; Robert Hecht (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
This paper discusses shifts in development assistance for health (DAH) since 1990, analyses the nature of the current distribution of funding, and considers future implications. Based on Jamison et al. (1998) and Frenk and Moon (2013), we introduce an essential functions framework, which provides a function-based taxonomy for global collective action in health, and apply that framework to several prominent actors and modalities for DAH. Potentially overlooked advantages to the complex DAH landscape and the special challenge of DAH for middle-income countries are discussed, as well as key challenges and questions about the future balance of essential functions of global health.
Keywords: F63; I10; I15; 330; development assistance for health; official development assistance; global health; WHO; Global Fund; GAVI